Republic of the Congo Economic Update, September 2015 - World Bank Group (World Bank, Washington, DC, 2016)
This second edition covers the year 2014 and the first quarter of 2015 and presents the economic outlook for 2015–2017. Beyond the review of recent economic developments, the report highlights the main results of the World Bank’s analytical work in the Republic of Congo with the aim to promote the consistency of the country’s economic policies in the medium and long term. This edition covers a variety of macroeconomic topics, from policies and economic indicators for the real sector to public finance, the monetary position and the external sector. It shows that Congo’s economy grew strongly in 2014 despite the significant decline in the price of oil. The lower oil prices will have an even greater impact in 2015 as they bring down domestic demand. Moreover, this edition looks in particular at the impact of volatile oil prices on the country’s economy, emphasizing the most appropriate fiscal policies in this context.